2013
DOI: 10.1016/j.jagp.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Psychological Therapy: Effectiveness in Schizophrenia Inpatient Settings Related to Patients' Age

Abstract: Objective: Elderly people with schizophrenia often suffer from cognitive impairments, which affect their social functioning. Today, only few therapy approaches for middleaged and older patients are available. The Integrated Psychological Therapy (IPT) combines neurocognitive and social cognitive interventions with social skills approaches. The aim of this study was to evaluate (1) whether IPT is effective in younger patients (age<40 years) and middle-aged patients (age≥40 years), and (2) whether control condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
2
15
0
4
Order By: Relevance
“…Regarding clinical and functional assessment, the results revealed significant differences in favour of IPT group in the negative and total PANSS and in the GAF and WHOQOL scales. These findings could be explained by the positive effect of the five IPT rehabilitation subprograms on overall symptoms (Mueller et al, 2013), quality of life in the psychological domain (Rakitzi et al, 2016), socio-working and general functioning (Zimmer et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding clinical and functional assessment, the results revealed significant differences in favour of IPT group in the negative and total PANSS and in the GAF and WHOQOL scales. These findings could be explained by the positive effect of the five IPT rehabilitation subprograms on overall symptoms (Mueller et al, 2013), quality of life in the psychological domain (Rakitzi et al, 2016), socio-working and general functioning (Zimmer et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Les scores obtenus par le groupe expérimental aux différents tests et échelles permettent de conclure que la participation au programme IPT engendre une amélioration du fonctionnement cognitif, d'une part, et une diminution de la symptomatologie, n. Ces résultats corroborent ceux de la littérature qui démontrent l'efficacité de l'IPT chez les patients souffrant de schizophrénie [17], quel que soit l'âge des patients [18]. Cette étude démontre que l'IPT repré-sente un programme thérapeutique accessible et bénéfique aux patients hospitalisés au long court (au moins sept ans) du fait d'une schizophrénie chronique et sévère.…”
Section: Discussionunclassified
“…IPT is also less emotionally straining compared to INT. IPT has also consistently demonstrated signifi cantly greater treatment eff ects on middle-aged and older patients then on control patients under standard treatment conditions (Mueller et al 2013 ). Th e results of the research on IPT, now stretching over three decades, have also repeatedly demonstrated a reduction of negative symptoms (summarized in Roder et al 2006aMueller and Roder 2008 ).…”
Section: Iptmentioning
confidence: 99%